1978
DOI: 10.1139/v78-406
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyse des sels de phospholium monomères: Préparation et propriétés des oxydes de 1,3-diénylphosphines

Abstract: The hydrolysis of 3,4-dimethylphospholium salts by thallium ethylate in alcohol yields exclusively the corresponding dienylphosphine oxides by ring opening in the general case. However when one of the phosphorus substituents is benzyl, the dienylphosphine oxide becomes the minor product of the hydrolysis, the major product being the 3-methyl-4-methylene-2-phospholene oxide which results from the cleavage of the P—CH2Ph bond with isomerization of one of the double bonds of the phosphole ring. Deuterolysis of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…They contain quaternized phosphorus in a five-membered unsaturated heterocycle. Some phospholium salts have been prepared previously but they were quaternized only with short alkyl chains, e.g., methyl or benzyl [47,48]. Therefore, the compounds synthesized and characterized here represent a unique type of cationic surfactants.…”
Section: Resultsmentioning
confidence: 99%
“…They contain quaternized phosphorus in a five-membered unsaturated heterocycle. Some phospholium salts have been prepared previously but they were quaternized only with short alkyl chains, e.g., methyl or benzyl [47,48]. Therefore, the compounds synthesized and characterized here represent a unique type of cationic surfactants.…”
Section: Resultsmentioning
confidence: 99%
“…No successful example of selective reduction of butadienylphosphine oxides into butadienylphosphines could be found in the literature. For example, it was reported that the reduction of 1,3‐butadienyldiphenylphosphine oxide with phenylsilane led to double bond hydrogenation 10a. Other reducing agents (LiAlH 4 , HSiCl 3 , Si 2 Cl 6 ) also proved to be unsuitable for the chemoselective conversion into butadienylphosphines 16.…”
Section: Methodsmentioning
confidence: 99%
“…The best documented ring-opening reaction takes place upon hydrolysis of phospholium salts (Scheme 23.24) [72,73]. In the transient hydroxyphosphorane, the phosphole ring probably occupies a axial-equatorial position, leading to cleavage of the elongated axial PÀC bond.…”
Section: Ring Openings and Expansionsmentioning
confidence: 99%